Systematic review of hypertension clinical practice guidelines based on the burden of disease: a global perspective. Issue 1 (February 2014) - Chen, Yin; Hu, Shilian; Li, Youping; Yan, Boxi; Shen, Gan; Wang, Li
Abstract Objective To perform a systematic review for the development, geographical distribution, and subject classification of clinical practice guidelines (CPGs) for hypertension worldwide. Methods CPGs for the management of hypertension were identified through the searching of Ovid, EMbase, and Chinese electronic databases. Major guidelines websites such as NGC (National Guideline Clearinghouse), GIN (Guidelines International Network), NICE (National Institute for Health and Clinical Excellence) and CPGN (Clinical Practice Guideline Network), as well as Google Scholar were also screened for additional information. EndNote X3 and Excel 2007 were used for extracting and analyzing the data of included CPGs. Results A total of 375 hypertension CPGs were included, involving 6 continents, 33 countries, 4 regions, and 3 international organizations. The publication date ranged from the year of 1971 to 2012, with the number of CPGs increased year by year. The CPGs were mainly developed by North America, Europe, and Asia. Their subjects covered 3 categories and 11 sub‐classes, which mainly focused on the management of adult hypertension (44.53%). Conclusion The number of CPGs varies in regions, countries, and academic organizations, with the development process differently. The regional disparity between the number CPGs and burden of hypertension were observed. The CPGs made a point of the management of adult hypertension.